ANALISIS TINDAK TUTUR BAHASA MUNA DIALEK MASALOKA (TINJAUAN SOSIOLINGUISTIK) - Muammar Muammar; Fatin Nabila; Maspiati Maspiati; La Ode Ikram Teguh Alam (JEC (Jurnal Edukasi Cendekia), 2020)
The purpose of this research is to be able to provide a descriptive description of the Muna Language Speech Act of the Masaloka Dialect that developed in the Bombana Regency area. The benefit of this research is that it is expected to be useful for increasing knowledge about sociolinguistics in each regional language, especially in terms of developing and fostering regional languages ​​in Indonesia. This research was obtained from data from interview sources in the family environment of native speakers of the Muna language itself. The data collection technique used in this research is using direct observation method (direct field method) with listening technique, recording technique and note-taking technique. The results in this study, the researchers analyzed the speech acts of the Muna language, the Masaloka dialect. The researcher conducted the research for 30 days, from November 4 s.d. December 4th. This research was obtained from interview resource data in the family environment of native speakers of the Muna language consisting of parents (father and mother), brothers and sisters and translated into Indonesian and then analyzed on several types of speech acts which are divided into four types of utterances, namely constative utterances totaling 2 utterances and performative utterances totaling 2 utterances; locutionary utterances are 3 utterances, illocutionary utterances are 2 utterances and perlocutionary utterances are 2 utterances; there are 3 representative utterances, 3 directive utterances, 2 utterances expressive, 3 commissive utterances and 2 utterances of declaration; there are 2 direct speeches, 2 indirect speeches, 2 literal utterances and 2 non-literal utterances; which is taken based on aspects of the speech situation in the utterances of the sentences in the Muna language.